To the question of channeling dislocation - Krasil’nikov, V.V.; Parkhomenko, A.A.; Robuk, V.N.; Sirota, V.V. (Вопросы атомной науки и техники, 2001)
The model of plastic deformation evolution and localization processes in irradiated materials is proposed. This models takes into account the dislocation distribution function dependence on dislocation velocity in an ensemble. It is shown that the fraction of dislocation overcoming radiation defects with high velocities in the dynamical regime grows with increasing radiation hardening.